Clinical practice, barriers to implementation, and priorities for equitable access of Stereotactic Body Radiation Therapy: an analysis of the global status by the ESTRO SBRT Focus Group - Franzese, Ciro; Tanadini-Lang, Stephanie; Verellen, Dirk; Wiersema, Lisa; Hörner-Rieber, Juliane; Romero, Alejandra Méndez; Pasquier, David; Bruynzeel, Anna; Boda-Heggemann, Judit; Depuydt, Tom; Sibolt, Patrik; Douir, Najma; et al. (Clinical and translational radiation oncology, 2026)
Background - Stereotactic Body Radiation Therapy (SBRT) has become an established treatment for several primary and metastatic malignancies; however, considerable heterogeneity remains in its definition, clinical indications, and technical delivery. - Methods - In May 2025, the SBRT Focus Group of the European Society for Radiotherapy and Oncology (ESTRO), in collaboration with International Stereotactic Radiosurgery Society (ISRS), the Radiosurgery Society (RSS), and the Japanese Society for Radiation Oncology (JASTRO), conducted a global survey. A 44-item questionnaire explored SBRT indications, technical aspects, dose/fractionation, and barriers to implementation. Descriptive statistics summarized the responses. - Results - Overall, 289 professionals from 59 countries participated. Routine use of SBRT was reported by 96.6 % of respondents, with lung, bone, liver and prostate as the most frequent indications. Pancreatic tumor (48.4 %), renal cell carcinoma (46.4 %), and ventricular tachycardia (12.4 %) represented emerging indications. C-arm linacs (89.2 %) and in-room Cone beam CT (CBCT) (92.0 %) were the dominant technologies. Motion management relied mainly on 4D-CT internal target volume (ITV) (88.9 %) and deep inspiration breath-hold (DIBH) (57.8 %). Fractionation was consistent for lung and prostate but heterogeneous for liver, and pancreas. Only 3.5 % reported routine use of online adaptive SBRT, while 61.5 % reported artificial intelligence (AI) use, mainly for organs-at-risk delineation. Key barriers included limited clinical trial funding (35.2 %), high equipment costs (34.2 %), insufficient reimbursement (27.7 %), and workforce shortages (33.9 %). - Conclusions - This ESTRO international survey provides the first global overview of SBRT practices. It demonstrates broad adoption but also substantial variability, highlighting the need for consensus guidelines, greater trial access, and expanded education to harmonize SBRT delivery and ensure equitable care worldwide.